Proposed Framework for Halal Value Chain Analysis in Batik Industry - Ahmad Syafruddin; Nilda Tri Putri; Rima Rofifah Putri; Ratni Prima Lita (Yayasan Riset dan Pengembangan Intelektual (YRPI), 2024)
This paper aims to apply the halal value chain to Tanah Liek Batik textiles to become halal batik products, using a framework designed to analyze the halal value chain. The method used in dealing with this problem is to apply HCCP (Halal Critical Control Point) to the company's activity value chain to become a halal value chain. The initial data used is a flow diagram of the production process of four types of Tanah Liek Batik products: Tanah Liek dyed batik, chemically dyed batik, stamped batik with soil-like dye, and chemically dyed batik. Based on the results of the identification of haram materials in each process in the activity, the Halal Control Point (HCP) is obtained. The application of HCCP to the Tanah Liek Batik value chain has 13 critical points of haram products, which come from the process, facilities, and tools and materials used during the production process. This study also produces a Halal Value Chain framework in the Textile Industry. Applying this framework in the textile industry is expected to increase the number of halal-certified textile industries.